QAR (QUESTION ANSWER RELATIONSHIP) AS AN ALTERNATIVE STRATEGY TO TEACH READING - Muzammil, Sa’dulloh (JL3T (Journal of Linguistics, Literature and Language Teaching), 2016)
In English language teaching, teaching reading plays an important role, for reading is one of language skills. In order to succeed doing this activity, a teacher must be familiar and able to employ various teaching readingstrategies that can assist his/her students comprehend what they read. To check students’ reading comprehension, a teacher may propose several questions related to the texts being read. However, if the students have difficulties dealing with these reading comprehension questions, a teacher must be able to help them by introducing reading strategies to overcome the problems. QAR is one of reading strategies which is beneficial for a teacher to check students’ reading comprehension and frame reading question-answer activity in reading phases: pre-, while-, and post-reading; as well as to help students locate answers for the questions.